2017
DOI: 10.1017/s0950268817000541
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance, penicillin-binding protein sequences, and pilus islet carriage in relation to clonal evolution of Streptococcus pneumoniae serotype 19A in Russia, 2002–2013

Abstract: SUMMARYClonal changes of serotype 19A pneumococci have been appreciated in conjunction with growing prevalence of this serotype after implementation of the seven-valent pneumococcal conjugate vaccine (PCV7). In the present study, we characterized serotype 19A pneumococci collected in Russia within a decade preceding the implementation of PCV vaccination and described their clonal evolution. We retrospectively analyzed non-invasive serotype 19A isolates collected in 2002-2013. All isolates were subjected to mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…A high incidence of IPD due to serotype 19A has been associated with a limited number of clonal complexes (CC199, CC320, and CC276). Contrary to that, a study from Russia carried out by Mayanskiy et al [50] demonstrated that local serotype distribution In our study, two isolates (1.8%) belonged to serotype 15A, which is not included in PCV-13. This serotype was previously associated with MDR and was isolated from most IPD cases in the post-PCV era in several post-industrial countries [51][52][53].…”
Section: Distribution Of Serotypescontrasting
confidence: 99%
“…A high incidence of IPD due to serotype 19A has been associated with a limited number of clonal complexes (CC199, CC320, and CC276). Contrary to that, a study from Russia carried out by Mayanskiy et al [50] demonstrated that local serotype distribution In our study, two isolates (1.8%) belonged to serotype 15A, which is not included in PCV-13. This serotype was previously associated with MDR and was isolated from most IPD cases in the post-PCV era in several post-industrial countries [51][52][53].…”
Section: Distribution Of Serotypescontrasting
confidence: 99%
“…In Russia, it was reported that among 49 S . pneumoniae isolates of serotype 19A isolated from healthy children, 59 % ( n =29) carried PI-1, whereas 14 % ( n =7) carried PI-2 [11]. In Japan, among 151 isolates of S.…”
Section: Introductionmentioning
confidence: 99%
“…In Russia, it was reported that among 49 S . pneumoniae isolates of serotype 19A isolated from healthy children, 59 % ( n =29) carried PI-1, whereas 14 % ( n =7) carried PI-2 [ 11 ]. In Japan, among 151 isolates of S. pneumoniae isolated from patients suffering on pneumococcal disease, 34 isolates that carried PIs belonged to serotypes 19F, 23F, 19A, 6E, 15B and 35B [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…We wondered whether the prevalence of CC3397 in serogroup 15 S. pneumoniae results from antibiotic pressure. Many studies have reported clonal shift phenomena in other serotypes, as CC271 replaced CC983 among serotype 19F strains ( Li et al, 2013 ), ST81 replaced ST342 amongst serotype 23F pneumococcal isolates ( Ma et al, 2013 ), CC320 replaced CC230 in 19A strains ( Beall et al, 2011 ; Golden et al, 2015 ; Mayanskiy et al, 2017 ), and CC876 replaced CC875 in serotype 14 strains ( He et al, 2015 ). These examples of clonal shift phenomena in the same serotype may be caused by antibiotic pressure, as they followed the principle that CCs/STs expressing high antibiotic resistance will replace CCs/STs with lower antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%